2005
DOI: 10.1074/jbc.m413569200
|View full text |Cite
|
Sign up to set email alerts
|

Human Sperm Do Not Bind to Rat Zonae Pellucidae Despite the Presence of Four Homologous Glycoproteins

Abstract: The specificity of sperm-egg recognition in mammals is mediated primarily by the zona pellucida surrounding ovulated eggs. Mouse sperm are quite promiscuous and bind to human eggs, but human spermatozoa will not bind to mouse eggs. The mouse zona pellucida contains three glycoproteins, ZP1, ZP2, and ZP3, which are conserved in rat and human. The recent observation that human zonae pellucidae contain a fourth protein raises the possibility that the presence of four zona proteins will support human sperm binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 52 publications
2
78
0
Order By: Relevance
“…These egg envelopes are mainly constructed of glycoproteins belonging to different subclasses of the zona pellucida (ZP) gene family (Spargo & Hope 2003, Conner et al 2005, Smith et al 2005. The components of this matrix include three or four glycoproteins (i.e., ZP1, ZP2, ZP3, and ZP4) in mammalian species (Lefievre et al 2004, Hoodbhoy et al 2005, Litscher & Wassarman 2007, Ganguly et al 2008, Izquierdo-Rico et al 2009). In the cases of nonmammalian vertebrate such as amphibians (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These egg envelopes are mainly constructed of glycoproteins belonging to different subclasses of the zona pellucida (ZP) gene family (Spargo & Hope 2003, Conner et al 2005, Smith et al 2005. The components of this matrix include three or four glycoproteins (i.e., ZP1, ZP2, ZP3, and ZP4) in mammalian species (Lefievre et al 2004, Hoodbhoy et al 2005, Litscher & Wassarman 2007, Ganguly et al 2008, Izquierdo-Rico et al 2009). In the cases of nonmammalian vertebrate such as amphibians (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The components of this matrix include three glycoproteins (i.e., ZP1, ZP2, and ZP3, which are also known as ZPB1, ZPA, and ZPC respectively, according to Spargo & Hope (2003) and Smith et al (2005)) in most mammalian species (Harris et al 1994) and four glycoproteins in several organisms including humans, bonnet monkeys, and rats (ZP1, ZP2, ZP3, and ZP4 (ZPB2); Lefievre et al 2004, Hoodbhoy et al 2005, Ganguly et al 2008, while non-mammalian vertebrates such as amphibians (i.e., Xenopus laevis and X. tropicalis), five ZP glycoproteins (ZP2, ZP3, ZP4, ZPD, and ZPAX) have been identified (Lindsay et al 2003, Goudet et al 2008. ZP gene family proteins are characterized by a highly conserved amino acid sequence called the ZP domain, consisting of about 260 amino acid residues with eight or ten conserved Cys residues (Bork & Sander 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, the ZP matrices of rats, hamsters, bonnet monkeys and humans are composed of four glycoproteins: ZP1, ZP2, ZP3 and ZP4. [8][9][10][11][12][13] In humans, ZP1 has a 638-aa polypeptide backbone; ZP2 has 745 aa; ZP3 has 424 aa and ZP4 has 540 aa. The ZP glycoproteins are heavily glycosylated and have N-as well as O-linked glycans, which have crucial roles in the spermatozoon-ZP interaction and AR induction.…”
Section: Composition Of the Zp Matrixmentioning
confidence: 99%
“…75 In this context, a fusion construct consisting of human IgG (Fc) and either exon 7 or 8 of mouse Zp3 were prepared. An EC cell line carrying the recombinant gene was produced that secreted chimeric glycoproteins designated either EC-huIgG (Fc)/mouse ZP3 (7) or EC-huIgG (Fc)/ mouse ZP3 (8). It was observed that only EC-huIgG (Fc)/mouse ZP3 (7) bound specifically to the plasma membrane overlying the sperm head to a similar extent as mouse ZP3 isolated from eggs, and at nanomolar concentrations EC-huIgG (Fc)/mouse ZP3 (7) inhibited the binding of mouse sperm to eggs in vitro.…”
Section: Zp3mentioning
confidence: 99%